2013
DOI: 10.3138/jsp.44.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Technological History: Papermaking to Digital Printing

Abstract: Disruptive technologies have been crucial to the shaping of publishing history. Paradoxically, while each of the technologies—specifically, the evolution of papermaking in Europe starting in the late thirteenth century, Gutenberg's printing press and type-casting from metal in the fifteenth century, lithographic offset printing in the twentieth century, and digital printing in the twenty-first century—has, on its own, been indeed revolutionary in nature, together they have served their role in the evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is a form of indirect printing, wherein the printing is not carried out directly on the paper but through rubber rollers. This substantially improved printing quality [29,30].…”
Section: From the Industrial Revolution To The Present Time: Technica...mentioning
confidence: 98%
“…It is a form of indirect printing, wherein the printing is not carried out directly on the paper but through rubber rollers. This substantially improved printing quality [29,30].…”
Section: From the Industrial Revolution To The Present Time: Technica...mentioning
confidence: 98%
“…Yet, there are few studies focused on the factors which are related to the printing industry. Hargrave (2013) found that disruptive technologies are considered as an important factor in printing industry. Pattabhiramaiah, Sriram and Sridhar (2017) examined the newspaper's optimal pricing equations, and revealed the role of subsidy and demand in the prices of printing paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thinking back to the advent of the Gutenberg press in 1440, printed communication gave rise to the spread of information and ideas to the masses across Europe (Hargrave, 2013). Similar to today"s communication practices, social media builds on the traditional model of pushing information out into the world to be absorbed by an audience.…”
Section: Twitter and Activismmentioning
confidence: 99%